The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-313x.2006.02701.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the glucosyltransferase UGT71B6 to disturb abscisic acid homeostasis in Arabidopsis thaliana

Abstract: SummaryA glucosyltransferase (GT) of Arabidopsis, UGT71B6, recognizing the naturally occurring enantiomer of abscisic acid (ABA) in vitro, has been used to disturb ABA homeostasis in planta. Transgenic plants constitutively overexpressing UGT71B6 (71B6-OE) have been analysed for changes in ABA and the related ABA metabolites abscisic acid glucose ester (ABA-GE), phaseic acid (PA), dihydrophaseic acid (DPA), 7¢-hydroxyABA and neo-phaseic acid. Overexpression of the GT led to massive accumulation of ABA-GE and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
153
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(167 citation statements)
references
References 61 publications
7
153
0
1
Order By: Relevance
“…Suppression of UGT71B6, UGT71B7, and UGT71B8 Causes Hypersensitivity to Exogenous ABA and High-Salt Stress during Germination A previous work showed that UGT71B6 loss-offunction mutant plants did not display any noticeable phenotype (Priest et al, 2006). When we examined single knockout mutants of UGT71B7 or UGT71B8, they did not show any noticeable phenotype (Supplemental Fig.…”
Section: Ugt71b6 Ugt71b7 and Ugt71b8 Are Soluble Proteins That Locamentioning
confidence: 99%
See 3 more Smart Citations
“…Suppression of UGT71B6, UGT71B7, and UGT71B8 Causes Hypersensitivity to Exogenous ABA and High-Salt Stress during Germination A previous work showed that UGT71B6 loss-offunction mutant plants did not display any noticeable phenotype (Priest et al, 2006). When we examined single knockout mutants of UGT71B7 or UGT71B8, they did not show any noticeable phenotype (Supplemental Fig.…”
Section: Ugt71b6 Ugt71b7 and Ugt71b8 Are Soluble Proteins That Locamentioning
confidence: 99%
“…Therefore, we examined their gene expression under osmotic stress conditions. The expression of UGT71B6 is induced under high osmotic stress conditions and by the application of exogenous ABA (Priest et al, 2006). To test whether the expression of UGT71B7 and UGT71B8 is regulated under these conditions, 2-week-old wild-type plants were treated with 100 mM ABA, 100 mM NaCl, or 300 mM mannitol for 1 h, and total RNA from these plants was used for qRT-PCR analysis.…”
Section: Ugt71b6mentioning
confidence: 99%
See 2 more Smart Citations
“…The sample preparation for ABA quantitation analysis was performed according to Priest et al (2006), with some modifications. Powder of lyophilized tissue (;5 mg) was extracted with 2 mL of acetone:water (80:20, v/v) in the presence of antioxidant-2,6-di-tert-butyl-4-methylphenol (0.1 mg mL 21 ) and 100 pmol isotope-labeled internal standard [ 2 H 6 ]-ABA.…”
Section: Aba Analysismentioning
confidence: 99%